INTEGRASI ASPEK RESIKO PADA PROSES PENGELOLAAN SUKU CADANG DI PLTD BITUNG - Richard Juandy Salensehe; Agung Sutrisno; Johan S C Neyland (JURNAL POROS TEKNIK MESIN UNSRAT, 2016)
The purpose of this research is to integrate aspects of risk in the process of managing spare parts in PLTD Bitung. To achieve these objectives, this research is using AHP methods (Analytical Hierarchy Proses). Â  Froms the result of the AHP the weight of the criteria are as follows : availability of goods (0,9542) delivery time (0,9986). Wear rate (1.3293), risk (1,1439). From AHP methods, priority supply of spareparts wish regards to all criteria, the highest priority given to nidlle bearing parts (1,4028). Â  Keyword : AHP, Risk, Needle bearing, Criteria